Factors released by low and high-LET irradiated fibroblasts modulate migration and invasiveness of pancreatic cancer cells - Charalampopoulou, Alexandra; Barcellini, Amelia; Ciocca, Mario; Di Liberto, Riccardo; Pasi, Francesca; Pullia, Marco Giuseppe; Orlandi, Ester; Facoetti, Angelica (Frontiers in Oncology, 2022)
Introduction Radiotherapy represents a major treatment option for patients with pancreatic cancer, however, its benefits remain limited also due to the ability of cancer cells to migrate to the surrounding tissues. Low-LET ionizing radiation is well known to promote tumor cell migration and invasion, nevertheless, little data provided by studies using high-LET radiation has led to ambiguous findings. What is hypothesized to be fundamental in the modulation of migration of tumor cells exposed to ionizing radiation is the influence of the microenvironment. Therefore, the properties of cells that populate the tumor stroma cannot be ignored when studying the influence of radiation on the migratory and invasive capacity of cancer cells. This is especially important in the case of pancreatic malignancies that are characterized by an abundance of stromal cells, including cancer-associated fibroblasts, which are known to orchestrate the cross-talk with tumor cells. Aim The current study aims to investigate whether the presence of factors released by irradiated fibroblasts affects the migratory and invasive capacity of pancreatic cancer cells exposed to different doses of photons or C-ions. Materials and methods AsPC-1 and AG01522 cells were irradiated with the same dose of photons or C-ions at room temperature. Through Boyden chamber assay, we tested whether factors secreted by irradiated fibroblasts may influence tumor cell migration, while the invasiveness of AsPC-1 cells was assessed using matrigel precoated inserts in which medium collected from non-irradiated (0 Gy), photon and C-ion irradiated fibroblasts, was added. Data were analyzed by Student t-test using GraphPad software. The mean ± s.d. was determined with a significance level of p<0.05. Results In the presence of conditioned medium collected from 1 Gy and 2 Gy photon irradiated fibroblasts, the number of migrated tumor cells increased (P<0.0360, P<0.0001) but decreased at 4 Gy dose (P<0.002). There was a trend of reduction in migration (P<0.0460, P<0.038, P<0.0024, P<0.0002), as well as a decrease in invasiveness (P<0.0525, P<0.0035, P<0.0868, P<0.0310) after exposure to 0.5 Gy, 1 Gy, 2 Gy and 4 Gy of C-ions. Conclusions The presence of irradiated fibroblasts affected the invasiveness capability of pancreatic cancer cells, probably by the reciprocal release of soluble factors whose production is differently modulated after high or low-LET radiation. Understanding the effects of irradiation on the metastatic potential of pancreatic cancer cells is of utmost importance for improving the outcome and tailoring the therapeutic approach. This challenging scenario requires a continuous and multidisciplinary approach that involves clinicians together with researcher experts in oncological and radiation treatment. In the last years, including preclinical experiences in a multidisciplinary approach has proved to be a winning strategy in clinical oncological research.